FAKTOR RISIKO YANG BERHUBUNGAN DENGAN KADAR HEMOGLOBIN DAN MALONDIALDEHID PADA PETUGAS PARKIR YANG TERPAPAR KARBON MONOKSIDA DI SWALAYAN SURAKARTA - Kusumawardhani, Anisa Dyah (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
The risk factor associated with levels of hemoglobin and malondialdehid of the parking attendants that being exposed to carbon monoxide in swalayan surakarta: Carbon monoxide is a poisonous gas and a free radical. Free radical causes lipid peroxide in the cell membrane in the body that led to the formation of malondialdehid. An erythrocyte peroxide in a membrane cause lysis of erythrocyte so that reduced levels of hemoglobin in the blood. The purpose of this study was to find the risk factor that have a correlation with levels of hemoglobin and malondialdehid of the parking attendants that being exposed to carbon monoxide in Swalayan Surakarta. This research utilized analytic survey design using cross sectional approach. The population of the this research was 36 parking attendants which was taken using total sampling method. And then was willing to be sample was 26 parking attendants. Data analysis was used chi square and fisher’s exact test. The result showed that 23,1% parking attendants have subnormal levels of hemoglobin and 50% parking attendants have a high malondialdehid levels. In the statistic test, there is correlation between period of working (p value = 0,047) and physic activities (p value = 0,016) with levels of malondialdehid. Recommendation is to provide an exhaust fan/ventilation for Swalayan A parking area by the management , parking attendants to wear a PPE such a cain mask with active carbon filter for reducing get worse impacts of health because cronic exposure of carbon monoxide, and consume a food with full of C and E nutrient as antioxidant consistently to eliminate the free radical in their body.